Transcriptional Regulation of the Type VI Secretion System 1 Genes by Quorum Sensing and ToxR in Vibrio parahaemolyticus - Zhang, Yiquan; Gao, He; Osei-Adjei, George; Zhang, Ying; Yang, Wenhui; Yang, Huiying; Yin, Zhe; Huang, Xinxiang; Zhou, Dongsheng (Frontiers in Microbiology, 2017)
Vibrio parahaemolyticus, the leading cause of seafood-associated gastroenteritis, harbours two separate T6SSs on chromosomes 1 and 2, i.e., T6SS1 (VP1386-1420) and T6SS2 (VPA1025-1046). T6SS1 contains at least 7 putative operons: VP1386-1387, VP1388-1390, VP1392-1391, VP1393-1406, VP1400-1406, VP1409-1407 and VP1410-1420. V. parahaemolyticus AphA and OpaR are the two master regulators of quorum sensing (QS) system that are highly expressed at low cell density (LCD) and high cell density (HCD), respectively. ToxR is a membrane-bound virulence regulatory protein conserved across the Vibrio family. In the present work, we show that ToxR coordinates with AphA and OpaR to repress T6SS1 expression in V. parahaemolyticus. OpaR binds to the promoters of VP1388-1390, VP1400-1406 and VP1409-1407 to repress their transcription, but it appears to negatively regulate VP1393-1406 transcription in an indirect manner. By contrast, AphA negatively regulated the above four T6SS1 operons in an indirect manner. In addition, ToxR binds to the promoters of VP1400-1406 and VP1409-1407 to inhibit their transcription, but it presents an indirect interaction with VP1388-1390 and VP1393-1406 promoters. Notably, the expression of ToxR also manifested in a QS-dependent manner and the highest expression occurred at LCD. Meanwhile, the highest expression of T6SS1 occurred at an OD600 value of 0.6 to 0.8 due to the tight regulation of ToxR and QS, suggesting T6SS1 functions only during the mid-logarithmic growth phase. These observations provide significant insight into the molecular mechanism of T6SS1 gene regulation by QS and ToxR in V. parahaemolyticus.